PENGISIAN AIRTANAH BUATAN (ARTIFICIAL RECHARGE) DALAM RANGKA MENGATASI BENCANA BANJIR LONGSOR DAN KETERSEDIAAN AIR TANAH DI KOTA PADANG - Edial, Helfia (Program Studi Pendidikan Geografi STKIP PGRI Sumatera Barat, 2015)
Problem of flooding and landslides in Indonesia are already an issue ordinary and natural, is due to geological conditions, geomorphological and meteorological Indonesia is very appropriate, ditambahlagi with the increasing number of population so many changes in land use of natural land into land settlements and land courts work. As a result, the problem of floods and landslides remain overshadow our lives. Several methods of flood and landslide risk reduction that can be done is to increase the capacity of infiltration of rainwater into the ground, therefore naturally infiltration process is reduced, then the artificial infiltration also can be done by methods as follows; Methods of spreading water on the surface